SURVIVAL AND RESPONSE MOLTING OF MUD CRAB (Scylla olivacea) INJECTED WITH MURBEY (Morus spp.) LEAVE EXTRACT - . Herlinah; Andi Tenriulo; Early Septiningsih; Hidayat Suryanto Suwoyo (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The soft shell crab productivity has been hampered due to the long rearing time and unsimultaneous molting of the crab. This study aimed to determine the effect of murbey (Morus spp.) leave extract as molting stimulant on Scylla olivacea and its best extract dosage to be applied in soft shell crabs production technology. Application of murbey extract was conducted by using injection method with 5 treatments such as (a) 0 ppm (as control); (b) 100 ppm; (c) 125 ppm; and (d) 150 ppm for 12 individual per treatment. The results showed that the highest molting percentage (50%) was obtained at the concentration of 100 ppm. Meanwhile, the control (0 ppm), 125 ppm, and 150 ppm treatments displayed the same molting response (33.3%). The fastest latent molting time (29 days) was found at the treatment of  125 ppm and the slowest one of 44 days at  100 and 150 ppm treatments. The best growth of crabs injected with murbey leaves extract was at the concentration of 100 ppm with the carapace width of 6.0 mm and the body weight of 32.98 g, while the lowest was obtained at the concentration of 150 ppm with the carapace width of 3.8 mm and the body weight of 25.43 g. Crabs treated with murbey extract at the concentrations of 100, 125, and 150 ppm exhibited survival rate of 91.7 % vs. the control of 83.3%. Murbey leaves extract have been proven to be effective in stimulating molting mud crab (Scylla olivacea). The 100 ppm exhibited the best response for growth and molting percentage, while the 125 ppm showed the best performance for latent period molting of the crab. Keywords: molting response, survival rate, Scylla olivacea, murbei leaves, Morus spp.